Return of Spontaneous Circulation Depends on Cardiac Rhythm During Neonatal Cardiac Arrest in Asphyxiated Newborn Animals - Wagner, Michael; Cheung, Po-Yin; Yaskina, Maryna; Lee, Tze-Fun; Vieth, Vanessa A.; O'Reilly, Megan; Schmölzer, Georg M. (Frontiers in Pediatrics, 2021)
Objective Pulseless electrical activity (PEA) occurs in asphyxiated newborn piglets and infants. We aimed to examine whether different cardiac rhythms (asystole, bradycardia, PEA) affects the resuscitation outcomes during continuous chest compressions (CC) during sustained inflations (CC+SI). Design This study is a secondary analysis of four previous randomized controlled animal trials that compared CC+SI with different CC rate (90 or 120/min), SI duration (20 or 60sec), peak inflation pressure (10, 20 or 30cmH2O), and oxygen concentration (18, 21 or 100%). Setting and Subjects Sixty-six newborn mixed breed piglets (1-3 days of age, weight 1.7-2.4 kg) were obtained on the day of experimentation from the University Swine Research Technology Centre. Interventions In all four studies, piglets were randomized into intervention or sham. Piglets randomized to “intervention” underwent both hypoxia and asphyxia, whereas, piglets randomized to “sham” received the same surgical protocol, stabilization, and equivalent experimental periods without hypoxia and asphyxia. Measurements To compare differences in asphyxiation time, time to return of spontaneous circulation (ROSC), hemodynamics, and survival rate in newborn piglets with asystole, bradycardia or PEA. Main Results Piglets with PEA (n=29) and asystole (n=13) had a significantly longer asphyxiation time and time to ROSC versus bradycardia (n=24). Survival rates were similar between all groups. Compared to their baseline, mean arterial pressure and carotid blood flow were significantly lower four hours after resuscitation in all groups, while being significantly higher in the bradycardia group. Conclusion This study indicates that cardiac rhythm before resuscitation influences the time to ROSC and hemodynamic recovery after ROSC.